Intervention model in reducing the unmet need for contraception: a systematic literature review on technology-based, community, and health worker interventions - Lia Nurdini; Legina Anggraeni; Loveria Sekarrini; Petriana Ekklesia Mahmud; Sabarinah Prasetyo (PAGEPress Publications, 2024)
The unmet need for contraception is a serious public health problem, and efforts to reduce the unmet need for family planning are a challenge due to the many and complex factors that contribute to the unmet needs. The aim of this study was to systematically review scientific evidence on intervention models that effectively reduce the unmet need for contraception. This study used a systematic review to identify relevant scientific articles. The article search was based on the PICO approach and used a database from https://www.scopus.com/, https://www.sciencedirect.com/, https://pubmed.ncbi.nlm.nih.gov/, https://www.mdpi.com/, https://www.jstor.org/, https://www.nature.com/, https://link.springer.com/. The reviewed material was full-text articles and open-access articles published from 2013 to 2023. Data extraction included author, country, type of intervention, research design, sample, and main research findings. Twelve studies were included in our qualitative synthesis. Technology-based interventions, such as mobile phone instant messaging apps, were implemented in countries like Tajikistan, Bolivia, and Mozambique. Community-based interventions included the Community Family Health=Family Wealth program in Uganda, the Tékponon Jikuagou (TJ) program in Benin, and the Married Adolescent Girls Club (MAG club) and Participatory Women's Group Intervention in Bangladesh. Health worker-led interventions involved community health volunteers in Nepal, postpartum contraceptive counseling, contraceptive counseling for all ages, structured counseling for childbearing couples in Indonesia, and the "Consult and Choose" client-centered family service in Jordan. The findings underscore that varying intervention models can significantly enhance contraceptive use, tailored to specific cultural and regional contexts. These interventions, therefore, hold substantial implications for public health practices aiming to address and reduce the global unmet need for contraception. This systematic review provides valuable insights into the effectiveness of diverse interventions and suggests avenues for public health strategies to expand contraceptive access and use globally.